PROCEDURE AND BASIS FOR APPLICATION OF PROCEDURAL COERCIVE MEASURES (TSUL LEGAL REPORT, 2026)
This article analyzes the types of coercive measures used in civil proceedings, including coercion, warning, expulsion from the courtroom, and court fines. The article also discusses the grounds, procedure and timing of the application of coercive measures, the need for coercive measures and the practical problems arising in the process of litigation, the experience of international countries in this area, as well as the application of coercive measures in society. The role and significance of coercive procedural measures in the judicial system, its application, procedure, scope, restrictions and exceptions in the using of coercive measures, including compulsory attendance, the bodies authorized to apply these measures, their rights and obligations established by the law, relations between judicial bodies and bodies authorized to implement coercive procedural measures, comparative analysis of national and foreign civil procedural legislation on applying of coercive measures in civil court proceedings, similarities and different aspects, making suggestions and recommendations on improving procedural coercive measures in civil proceedings are analyzed.